The geese of Wrangel Island - Uspenski, Dr S M (Wildfowl, 1965)
In 1960 there were about 130,000 occupied nests of Lesser Snow Geese in their main colony on Wrangel Island. In 1964, when the spring weather was extremely unfavourable for reproduction, about 114,000 nests were in use, with about 300,000 geese in the nesting areas. In 1964 the average clutch-size was 3.27 eggs, compared with 5-6 in normal years. Nests in areas where the snow persisted longest and where the bird population was less dense contained fewest eggs. A large number of mature birds failed to nest although their gonads were normally developed. Non-breeders were most numerous in areas where the snow melted late. The average size of young broods was 2.7 goslings, range 1-5. Nesting in 1958 was probably even later than in 1964. 1-2,000 pairs of Pacific Brent Geese were nesting on the island in 1964 and another 10,000 non-breeders were moulting there. Moulting Brent caught included four previously ringed in Alaska, also when moulting.